2010
DOI: 10.4103/0973-1482.73363
|View full text |Cite
|
Sign up to set email alerts
|

Cavitary mucoepidermoid carcinoma of lung with metastases in skeletal muscles as presenting features: A case report and review of the literature

Abstract: Mucoepidermoid carcinomas (MECs) of lung are rare neoplasms originating in bronchial submucosal glands and comprising 0.1-0.2% of primary lung cancers. MECs, the most common malignancy in salivary glands, were earlier thought to occur only in salivary glands. Later studies showed that they can arise as a primary in bronchus, esophagus, lacrimal glands, pancreas, thymus and thyroid gland. Initially described as a benign adenoma, it is now considered to be a malignant epithelial tumor. There have been reports of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Mucoepidermoid carcinoma is a relatively common neoplasm of the salivary glands, which rarely arises in other sites, including esophagus, anal canal, skin of the breast, lachrymal sac, thymus, thyroid gland, lung or uterine cervix [1-4]. Primary intrahepatic mucoepidermoid carcinoma is rare tumor with only 17 cases described in the English literature so far [5-17].…”
Section: Introductionmentioning
confidence: 99%
“…Mucoepidermoid carcinoma is a relatively common neoplasm of the salivary glands, which rarely arises in other sites, including esophagus, anal canal, skin of the breast, lachrymal sac, thymus, thyroid gland, lung or uterine cervix [1-4]. Primary intrahepatic mucoepidermoid carcinoma is rare tumor with only 17 cases described in the English literature so far [5-17].…”
Section: Introductionmentioning
confidence: 99%
“…[5] Primary presentation of a skeletal muscle metastasis, such as in our case, remains an unusual occurrence. [36789] The present case, where the initial presentation was of metastatic muscular involvement, highlights the role of FDG PET/CT in tracing the location of primary lung malignancy and unsuspected sites of multiple muscle metastases in a patient with muscle metastases of unknown primary.…”
Section: Discussionmentioning
confidence: 81%
“…In their study, Singh et al [10] recommended that, in the treatment of both low-grade and high-grade MECs, resection should be performed first; they also recommended that an additional excision be performed if the surgical border remained positive. Furthermore, they indicated that no adjuvant therapy is needed if the MEC tumor is low-grade and the patient is eligible for surgical treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Metastases are most frequently seen in the regional lymphatic nodes (48%), bone (25%), distant lymphatic nodes (18%), and the adrenal gland, cerebral, and skin (14%). [10] As Singh et al [10] stated, radiotherapy and chemotherapy are preferred in patients whose surgical margins remained positive and whose tumors cannot be re-resected, or in inoperable patients who already are metastatic at the time of diagnosis. In those patients, cisplatin, docetaxel, gemcitabine, adriamycin, and pemetrexed are preferred chemotherapy combinations.…”
Section: Discussionmentioning
confidence: 97%